Electronic paper display screen sealant and preparation method thereof
By combining the formulation design of low viscosity bisphenol F type epoxy resin and polyphenol oxygen resin in electronic paper sealant, the shortcomings of traditional sealant in rapid curing, bonding strength and durability are solved, and electronic paper display is realized High-efficiency sealing and stable performance of the screen.
Patent Information
- Application Number
- CN202411786782.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-02-11
AI Technical Summary
Traditional electronic paper sealants have shortcomings in rapid curing, bonding strength and durability, especially in the poor bonding effect of flexible substrates such as PET, which affects the widespread application of electronic paper technology.
Using a specific formula UV electronic paper packaging glue, the combination of low viscosity bisphenol F-type epoxy resin and polyphenol oxygen resin and optimized process to achieve rapid curing and high bonding strength.
It realizes rapid curing of electronic paper display sealant, significantly improves bonding strength and durability, and ensures the stable performance of electronic paper screens in various environments.
Smart Images

Figure BDA0005174247810000021 
Figure BDA0005174247810000031 
Figure BDA0005174247810000051
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electronic paper packaging adhesives, and relates to an electronic paper display screen sealant and a preparation method thereof. Background Art
[0002] Electronic paper, also known as digital paper, is an ultra-thin and ultra-light display screen that has attracted much attention for its paper-like feel, ultra-low power consumption, visibility in sunlight, eye protection and no blue light. Its basic principle is based on the "microcapsule electrophoresis display" technology, which presents images through the migration of charged nanoparticles suspended in liquid under the action of an electric field. Electronic ink is composed of millions of microcapsules, each of which contains negatively charged white titanium oxide particles and positively charged black toner particles. When the electric field is turned on, the black and white particles will move to the top of the microcapsule using the principle of positive and negative attraction, thereby forming the desired image or text on the screen.
[0003] The unique advantage of electronic paper technology is that it can maintain the display even when the power is off, which makes it have a wide range of application prospects in the fields of e-book readers, electronic tags, electronic billboards, etc. In addition, as the technology continues to mature and the cost gradually decreases, electronic paper is gradually penetrating into more fields, such as electronic paper watches, electronic paper bus cards, etc., bringing users a more convenient and environmentally friendly experience.
[0004] However, the special structure of electronic paper screens also places higher demands on packaging materials. Traditional packaging materials often fail to meet their requirements in terms of fast curing, low warpage, high bonding strength, etc. Therefore, the development of special packaging glue suitable for electronic paper screens has become the key to promoting the further development of electronic paper technology.
[0005] In the manufacturing process of electronic equipment, electronic sealants play a vital role. They can not only provide a stable bonding effect, but also ensure the stable operation of the equipment under various environmental conditions. However, traditional electronic sealants are mainly in the form of thermal curing, which has significant disadvantages: long curing time, low production efficiency, most thermal curing glues are cured at low temperatures of 70 / 80℃, poor storage stability, short service life, and a significant increase in viscosity within a few hours of opening. It is easy to cause parts such as screens to warp during the curing process, affecting the overall quality of the product and user experience. In addition, with the continuous advancement of technology, some manufacturers have tried to develop UV-curing encapsulation glue in order to shorten the curing time and improve production efficiency. However, for special materials such as electronic paper screens, their surface is usually covered with a thin film that blocks UV light, which directly leads to the inability of UV-curing glue to fully cure. Moreover, with the development of flexible electronic paper displays, the glass substrate has been replaced with flexible films such as PET, and the bonding effect has been greatly reduced, which has become a major problem restricting the widespread application of electronic paper technology.
[0006] Therefore, in the art, it is desired to develop an electronic paper display screen sealant that can not only achieve rapid curing but also significantly improve bonding strength and durability. Summary of the invention
[0007] In view of the shortcomings of the prior art, the purpose of the present invention is to provide an electronic paper display screen sealant and a preparation method thereof. Specifically, in view of the problems of the electronic paper sealant currently on the market, such as the long time-consuming thermal curing process, low production efficiency, short usable time, obvious viscosity increase, and poor UV curing bonding effect, the present invention provides a new UV electronic paper encapsulation glue solution.
[0008] The electronic paper display screen sealant provided by the present invention overcomes the limitations of traditional heat-curing adhesives and existing UV-curing adhesives in electronic paper screen packaging. Through unique formula design and process optimization, the present invention not only achieves rapid curing and effectively shortens the production cycle, but also significantly improves the bonding strength and durability, ensuring the stable performance of the electronic paper screen in various environments.
[0009] To achieve this object, the present invention adopts the following technical solutions:
[0010] In a first aspect, the present invention provides an electronic paper display screen sealant, wherein the raw materials for preparing the electronic paper display screen sealant include the following components in parts by weight:
[0011]
[0012]
[0013] The epoxy resin includes a low-viscosity bisphenol F type epoxy resin.
[0014] Since the flexible substrate (such as PET) of the electronic paper display screen has high toughness, while the epoxy resin has the characteristics of poor toughness and high brittleness, the traditional electronic paper encapsulation glue has low adhesion to the flexible substrate and poor sealing effect. The present invention adopts a specific amount of polyphenol oxide resin, which has high polarity and can improve the adhesion of the sealant, and is combined with other components, so that the prepared electronic paper sealant can not only cure quickly, but also has the characteristics of high curing rate, high bonding strength, low water vapor permeability, good storage stability, etc.
[0015] Since the viscosity of polyphenol oxide resin after melting is relatively high, if the amount added is too small, the improvement in adhesion will be low. If the amount added is too large, the viscosity of the sealant will rise sharply, the fluidity will be low, and the sealing and filling effect will be poor.
[0016] In the present invention, the raw materials for preparing the electronic paper display screen sealant are calculated by weight, and the amount of epoxy resin used can be 40 parts, 42 parts, 44 parts, 46 parts, 48 parts, 50 parts, 52 parts, 54 parts, 56 parts, 58 parts, 60 parts, 62 parts, 64 parts, 66 parts, 68 parts, 70 parts, etc.
[0017] In the present invention, the raw materials for preparing the electronic paper display screen sealant are measured by weight, and the amount of polyphenol oxide resin used can be 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1 parts, 1.1 parts, 1.2 parts, 1.3 parts, 1.4 parts, 1.5 parts, etc.
[0018] In the present invention, the raw materials for preparing the electronic paper display screen sealant are measured by weight, and the amount of the diluent used can be 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 12 parts, 14 parts, 16 parts, 18 parts, 20 parts, etc.
[0019] In the present invention, the raw materials for preparing the electronic paper display screen sealant are measured by weight, and the amount of the cationic photoinitiator used can be 1 part, 1.2 parts, 1.3 parts, 1.5 parts, 1.8 parts, 2 parts, 2.2 parts, 2.3 parts, 2.5 parts, 2.8 parts, 3 parts, etc.
[0020] In the present invention, the raw materials for preparing the electronic paper display screen sealant are calculated by weight, and the amount of the sensitizer used can be 0.1 part, 0.2 part, 0.3 part, 0.4 part, 0.5 part, etc.
[0021] In the present invention, the raw materials for preparing the electronic paper display screen sealant are calculated by weight, and the amount of other additives used can be 26 parts, 28 parts, 30 parts, 32 parts, 34 parts, 36 parts, 38 parts, 40 parts, 42 parts, 44 parts, 46 parts, 48 parts, 50 parts, 52 parts, 54 parts, 56 parts, 58 parts, 60 parts, 62 parts, etc.
[0022] Preferably, the viscosity of the low-viscosity bisphenol F epoxy resin at 25° C. is lower than 1500 cps, for example, 1450 cps, 1400 cps, 1300 cps, 1200 cps, 1100 cps, 1000 cps, etc.
[0023] Preferably, the epoxy resin further comprises any one of bisphenol A epoxy resin, hydrogenated bisphenol A epoxy resin, alicyclic epoxy resin, and multifunctional epoxy resin, or a combination of at least two thereof.
[0024] Preferably, the viscosity of the bisphenol A epoxy resin or hydrogenated bisphenol A epoxy resin at 25° C. is lower than 10,000 cps, such as 9,000 cps, 8,000 cps, 7,000 cps, 6,000 cps, etc.
[0025] Preferably, the viscosity of the alicyclic epoxy resin or multifunctional epoxy resin at 25° C. is lower than 500 cps, such as 400 cps, 300 cps, 250 cps, 200 cps, etc.
[0026] By comprehensively controlling the viscosity of the epoxy resin, the viscosity of the sealant is maintained within an appropriate range.
[0027] Preferably, the epoxy resin includes low viscosity bisphenol F epoxy resin and alicyclic epoxy resin. The epoxy groups of alicyclic resin are directly connected to the alicyclic ring, which can form a tight rigid structure, have high crosslinking density after curing, and provide a certain degree of hydrophobicity with fillers.
[0028] Preferably, the mass ratio of the alicyclic epoxy resin to the low viscosity bisphenol F epoxy resin is 1:(1-2), for example, 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9, 1:2, etc., more preferably 1:(1-1.6).
[0029] Preferably, the polyphenol oxide resin has the following structure:
[0030]
[0031] Preferably, the weight average molecular weight of the polyphenol oxide resin is 40,000-60,000, for example, 40,000, 42,000, 44,000, 46,000, 48,000, 50,000, 52,000, 54,000, 56,000, 58,000, 60,000, etc.
[0032] Preferably, the polyphenoloxy resin comprises PKHH.
[0033] PET film, which is the flexible substrate of electronic paper display, has high toughness, the strongest among all thermoplastics, and is dimensionally stable. Although epoxy resin has excellent mechanical properties, the cured resin has the disadvantages of poor toughness and high brittleness, and has poor adhesion to PET. Polyphenol oxide resin, as a thermoplastic resin, has high polarity, so it has good adhesion to many high-polar substances such as metal, wood, glass, ceramics, polyester, etc. Due to similar compatibility, polyphenol oxide resin can improve the adhesion of epoxy resin to PET.
[0034] Preferably, the diluent includes any one of 3-ethyl-3-epoxypropylene methanol, 2-ethylhexyl vinyl ether, polypropylene glycol glycidyl ether, oxetane, and ethylene glycol diglycidyl ether, or a combination of at least two thereof.
[0035] Preferably, the cationic photoinitiator includes any one of iodonium salts, sulfonium salts, iron aromatic salts, and diazonium salts, or a combination of at least two thereof.
[0036] Preferably, the sensitizer includes any one of thiophene derivatives, anthracenes, and polyhydroxy compounds, or a combination of at least two of them.
[0037] Preferably, the other auxiliary agents include any one of a toughening agent, a filler, and a coupling agent, or a combination of at least two of them.
[0038] Preferably, the other additives include 15-30 parts of tougheners (for example, 15 parts, 16 parts, 18 parts, 20 parts, 22 parts, 24 parts, 26 parts, 28 parts, 30 parts, etc.), 10-30 parts of fillers (for example, 10 parts, 12 parts, 14 parts, 16 parts, 18 parts, 20 parts, 22 parts, 24 parts, 26 parts, 28 parts, 30 parts, etc.), and 1-2 parts of coupling agents (for example, 1 part, 1.5 parts, 2 parts, etc.).
[0039] Preferably, the toughening agent includes any one of polyester polyol, polyfarnesene glycol, polycarbonate polyol, propoxylated bisphenol A epoxy, polyurethane modified epoxy, and core-shell structured silicone rubber, or a combination of at least two thereof.
[0040] Preferably, the filler includes any one of kaolin, silicon dioxide, talc, alumina, mica powder or silicone microspheres, or a combination of at least two thereof.
[0041] Preferably, the selected filler is a flaky filler such as mica powder, kaolin, talc, etc. As a preferred technical solution of the present invention, by selecting a flaky filler, compared with fillers in other forms, the colloid can be given water-blocking properties through layered compounds stacked layer by layer, and the water can be inhibited from passing through the interface. At the same time, the addition of fillers can greatly reduce the thermal expansion coefficient of the system.
[0042] Preferably, the coupling agent includes any one of a silane coupling agent, a titanate coupling agent or an aluminate coupling agent, or a combination of at least two of them.
[0043] In a second aspect, the present invention provides a method for preparing the electronic paper display screen sealant as described in the first aspect, the preparation method comprising the following steps:
[0044] (1) melt-blending the polyphenol oxide resin with a portion of low-viscosity bisphenol F epoxy resin at high temperature;
[0045] (2) Adding a diluent, a cationic photoinitiator, and a sensitizer to step (1), and then adding the remaining low-viscosity bisphenol F epoxy resin, other optional epoxy resins, and other additives, and mixing to obtain the electronic paper display screen sealant.
[0046] In the preparation method provided by the present invention, the polyphenol oxide resin and part of the low-viscosity bisphenol F epoxy resin are melted at high temperature and then mixed with other components. The low-viscosity bisphenol F epoxy resin not only has good thermal stability, but also has good compatibility with the polyphenol oxide resin, does not turn yellow when melted at high temperature, and can maintain a low viscosity while enhancing the adhesive strength of the sealant.
[0047] Preferably, the mass ratio of the polyphenol oxide resin to part of the low-viscosity bisphenol F epoxy resin in step (1) is 1:(10-15), for example, 1:10, 1:11, 1:12, 1:13, 1:14, 1:15, etc.
[0048] Preferably, the temperature of the melt blending in step (1) is 180-200°C, for example, 180°C, 185°C, 190°C, 195°C, 200°C, etc., and the time of melt blending is 60-120min, for example, 60min, 70min, 80min, 90min, 100min, 110min, 120min, etc.
[0049] Preferably, the mixing time in step (2) is 30-60 min, for example, 30 min, 40 min, 50 min, 60 min, etc.
[0050] Compared with the prior art, the present invention has at least the following beneficial effects:
[0051] (1) The sealant provided by the present invention adopts UV curing, which can greatly shorten the production cycle compared with the traditional thermal curing method;
[0052] (2) The present invention can effectively improve the problem of poor UV light curing bonding effect by introducing a specific polyphenol oxide resin and compounding it in different proportions, and can improve the hydrophobicity of the sealant. Compounding with a sensitizer can improve the degree of UV light curing, further improving the problem of poor existing UV curing bonding effect. DETAILED DESCRIPTION
[0053] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0054] Unless otherwise specified, the raw material information used in the examples and comparative examples of the present invention is shown in Table 1 below:
[0055] Table 1
[0056]
[0057]
[0058] Examples 1-5, Comparative Examples 1-6
[0059] In Examples 1-5 and Comparative Examples 1-6, an electronic paper display screen sealant is provided respectively. The specific selection and dosage (parts by weight) of the raw materials for preparing the electronic paper display screen sealant are shown in Table 2.
[0060] Table 2
[0061]
[0062]
[0063] The preparation method comprises the following steps:
[0064] (1) According to the formula in Table 2, weigh polyphenoloxy resin and part of bisphenol F epoxy resin (polyphenoloxy resin: bisphenol F epoxy resin = 1:10), add them into a container and heat them in an oven at 180° C. for 1 h until they are uniform;
[0065] (2) Weigh the diluent, cationic photoinitiator and sensitizer according to the formula in Table 2, and stir them evenly with an electric stirrer;
[0066] (3) According to the formula in Table 2, the remaining bisphenol F epoxy resin, alicyclic epoxy resin, toughening agent, filler, coupling agent and the semi-finished products prepared in steps (1) and (2) were weighed and mixed together, stirred for 40 minutes by a planetary mixer, and ground and dispersed three times by a three-roll grinder to obtain the electronic paper display screen sealant.
[0067] Comparative Example 7
[0068] The difference between this comparative example and Example 1 is that the preparation method is different, which is as follows:
[0069] (1) According to the formula in Table 2, weigh polyphenol oxide resin and part of alicyclic epoxy resin (polyphenol oxide resin: alicyclic epoxy resin = 1:10), add them into a container and heat them in an oven at 180° C. for 1 h until they are uniform;
[0070] (2) Weigh the diluent, cationic photoinitiator and sensitizer according to the formula in Table 2, and stir them evenly with an electric stirrer;
[0071] (3) According to the formula in Table 2, the remaining alicyclic epoxy resin, bisphenol F epoxy resin, toughening agent, filler, coupling agent and the semi-finished products prepared in steps (1) and (2) were weighed and mixed together, stirred for 40 minutes by a planetary mixer, and ground and dispersed three times by a three-roll grinder to obtain the electronic paper display screen sealant.
[0072] Performance Testing
[0073] The performance test of the electronic paper display screen sealant provided in the embodiment and the comparative example is carried out, and the test method is as follows:
[0074] (1) Viscosity: The viscosity of the sealant was tested using a DV2T rotational viscometer at 25°C.
[0075] (2) Curing rate: Use infrared spectrometer FT-IR to test the glue sample before and after curing, and calculate it using the following curing rate formula:
[0076] Where:
[0077] H0——reference peak height of sealant before curing;
[0078] R0——Height of characteristic peak of sealant before curing;
[0079] H1——reference peak height of the glue block after curing;
[0080] R1——Characteristic peak height of the rubber block after curing;
[0081] The characteristic peak is 910cm -1 Epoxy absorption peak;
[0082] The reference peak was 1610 cm -1 Benzene ring absorption peak;
[0083] (3) Curing energy: Use 405nm LED lamp and energy meter to characterize the curing energy;
[0084] (4) Bond strength: The shear force of glass and PET with 365 nm LED light blocking was tested using a universal tensile testing machine;
[0085] (5) Water vapor transmission rate: Use a coating machine to prepare a sample with a size of 150 mm*150 mm*1 mm, 405 nm LED light 5000 mj / cm 2 Curing, using water vapor transmission rate instrument test, test conditions: 50℃, 100%RH, unit: g / m 2 .24h, thickness 1mm.
[0086] The performance test results are shown in Table 3.
[0087] Table 3
[0088]
[0089]
[0090] It can be seen from Table 3 that the electronic paper display sealant provided by the present invention can be quickly cured at a relatively low energy under a 405nm LED, and has a good curing effect (curing rate: 83%-92%), low viscosity (1135-1850cps), good sizing effect, good storage stability (>12 months), and excellent glass PET bonding performance and excellent water vapor barrier effect. The general water vapor transmission rate is 5-6g / m 2 .24h, which improves the problem of long time and low production efficiency of traditional thermal curing glue, and improves the problem of poor bonding effect of UV glue.
[0091] Compared with Example 2, Comparative Example 1 does not add polyphenol oxide resin and has poor bonding strength.
[0092] Compared with Example 1, Comparative Example 2 does not add a sensitizer, and the curing effect is poor, resulting in deviations in bonding strength and water vapor transmission rate.
[0093] Compared with Example 1, in Comparative Example 3, excessive amount of polyphenol oxide resin is added, and the viscosity is too high, greater than 2500cps, which affects the sizing. The fluidity of the sealant is poor at room temperature, and promoting fluidity by heating is not conducive to the use of manufacturers.
[0094] Compared with Example 1, the amount of polyphenol oxide resin added in Comparative Example 4 is too little, and the bonding effect is poor.
[0095] Compared with Example 2, Comparative Example 5 uses a high-viscosity bisphenol F-type epoxy resin, which has a viscosity that is too high, greater than 2500 cps, which affects sizing and is not conducive to use by manufacturers.
[0096] Compared with Example 1, Comparative Example 6 adds low molecular weight polyphenol oxide resin, and the bonding effect is poor.
[0097] Compared with Example 1, Comparative Example 7 uses alicyclic epoxy resin and polyphenol oxygen resin to melt blend. During the heating and melting process of the alicyclic epoxy resin and the polyphenol oxygen resin, the melt turns yellow, and the viscosity of the sealant finally obtained is too high, the bonding effect is general, and the storage stability is poor. Although the viscosity of the alicyclic epoxy resin raw material is lower than that of the low-viscosity bisphenol F epoxy resin, the viscosity of the sealant finally obtained is higher. This may be because the manufacturing process of the alicyclic epoxy resin raw material is relatively complicated, the raw material purity is generally low, and part of the alicyclic epoxy resin reacts during the high-temperature melting process, resulting in an abnormal increase in viscosity. However, during the melting process of the low-viscosity bisphenol F epoxy resin used in the present invention and the polyphenol oxygen resin, the melt blend will not experience a sudden increase in viscosity.
[0098] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate the electronic paper display screen sealant and its preparation method of the present invention, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. An electronic paper display screen sealant, characterized in that: The raw materials for preparing the electronic paper display screen sealant include the following components in parts by weight: The epoxy resin includes a low-viscosity bisphenol F type epoxy resin.
2. The electronic paper display screen sealant according to claim 1, characterized in that: The low-viscosity bisphenol F epoxy resin has a viscosity of less than 1500 cps at 25° C.; Preferably, the epoxy resin further comprises any one or a combination of at least two of bisphenol A epoxy resin, hydrogenated bisphenol A epoxy resin, alicyclic epoxy resin, and multifunctional epoxy resin; Preferably, the viscosity of the bisphenol A epoxy resin or hydrogenated bisphenol A epoxy resin at 25° C. is less than 10,000 cps; Preferably, the viscosity of the alicyclic epoxy resin or multifunctional epoxy resin at 25° C. is lower than 500 cps.
3. The electronic paper display screen sealant according to claim 1 or 2, characterized in that: The epoxy resin includes a low-viscosity bisphenol F epoxy resin and an alicyclic epoxy resin; Preferably, the mass ratio of the alicyclic epoxy resin to the low-viscosity bisphenol F-type epoxy resin is 1:(1-2), more preferably 1:(1-1.6).
4. The electronic paper display sealant according to any one of claims 1 to 3, characterized in that: The polyphenol oxide resin has the following structure: Preferably, the weight average molecular weight of the polyphenol oxide resin is 40000-60000; Preferably, the polyphenoloxy resin comprises PKHH.
5. The electronic paper display screen sealant according to any one of claims 1 to 4, characterized in that: The diluent includes any one of 3-ethyl-3-epoxypropylene methanol, 2-ethylhexyl vinyl ether, polypropylene glycol glycidyl ether, oxetane, and ethylene glycol diglycidyl ether, or a combination of at least two thereof; Preferably, the cationic photoinitiator comprises any one of iodonium salts, sulfonium salts, iron aromatic salts, and diazonium salts, or a combination of at least two thereof; Preferably, the sensitizer includes any one of thiophene derivatives, anthracenes, and polyhydroxy compounds, or a combination of at least two of them.
6. The electronic paper display screen sealant according to any one of claims 1 to 5, characterized in that: The other additives include any one of a toughening agent, a filler, and a coupling agent, or a combination of at least two thereof; Preferably, the other additives include 15-30 parts of toughening agent, 10-30 parts of filler, and 1-2 parts of coupling agent.
7. The electronic paper display screen sealant according to claim 6, characterized in that: The toughening agent includes any one or a combination of at least two of polyester polyol, polyfarnesene glycol, polycarbonate polyol, propoxylated bisphenol A epoxy, polyurethane modified epoxy, and core-shell structured silicone rubber; Preferably, the filler comprises any one or a combination of at least two of kaolin, silicon dioxide, talc, alumina, mica powder or silicone microspheres; Preferably, the coupling agent includes any one of a silane coupling agent, a titanate coupling agent or an aluminate coupling agent, or a combination of at least two of them.
8. A method for preparing an electronic paper display screen sealant as claimed in any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: (1) melt-blending the polyphenol oxide resin and a portion of the low-viscosity bisphenol F epoxy resin; (2) Adding a diluent, a cationic photoinitiator, and a sensitizer to step (1), and then adding the remaining low-viscosity bisphenol F epoxy resin, other optional epoxy resins, and other additives, and mixing to obtain the electronic paper display screen sealant.
9. The preparation method according to claim 8, characterized in that: The mass ratio of the polyphenol oxide resin to the part of the low-viscosity bisphenol F epoxy resin in step (1) is 1:(10-15); Preferably, the temperature of the melt blending in step (1) is 180-200° C., and the time of the melt blending is 60-120 min.
10. The preparation method according to claim 8 or 9, characterized in that: The mixing time in step (2) is 30-60 minutes.